The importance of establishing landscape architecture in construction projects with an urban management approach: An inter-disciplinary study - Partovian, Arian (2021)
The objective of this study was to the Importance of Establishing Landscape Architecture in Construction Projects with an Urban Management Approach. The methods of this study are a descriptive-analytical research method that the data used in the research section of this project is obtained from the library method. The library information used in this project is derived from a variety of methods, including reference to books, journals, research projects, maps, and Internet searches. The results showed that the smell of the citizens had the greatest impact on the quality of the urban landscape, because the question is to what extent have the elements of nature, such as plants and flowers, created pleasant aromas. It has the highest rankings in the Friedman test, and the lowest rankings for the question of how many unpleasant odors can be smelled? This also confirms the importance of olfactory perspective on urban landscape quality. Therefore, paying attention to the appearance and urban landscape is very important both in terms of architecture and aesthetics and in terms of improving the quality of urban furniture in the process of urban management. However, recognizing the nature of these activities and their developmental effects in the city is also very important.